The Quotation Theory of Writing. (January 2014) - Olson, David R.; Oatley, Keith
Learning to read and write is seen as both the acquisition of skills useful in a modern society and an introduction to a world increasingly organized around the reading and writing of authoritative texts. While most agree on the importance of writing, insufficient attention has been given to the more basic question of just what writing is, that is, how best to think about writing as both a technology of communication and an instrument of thought. In this article we elaborate and defend the view that writing is distinctive not only as a technology for the visual representation of speech but more basically as a technology for taking language "off-line, " that is, as language enclosed by quotation marks. Writing, like oral quotation, provides a set of objects divorced from the speaker that persist in time and space and that can be considered and reconsidered somewhat independently of the context of expression and the intentions of the original author. Of special relevance are the units of meaning, namely, words and sentences. When writing turns words and sentences into objects of analysis, it facilitates distinctive modes of discourse such as extended prose and distinctive modes of thinking such as formal rationality.